Nogai the Khanmaker: A Historiographical Problem - Wilson J. (Золотоордынское обозрение)
Abstract: Research objectives: Nogai, a great-grandson of Jochi, is most commonly known as the all-mighty kingmaker of the late thirteenth century Golden Horde, who in scholarship is portrayed as appointing and deposing khans at will and establishing an independent khanate on the lower Danube. However, the author argues that this is a portrayal with little basis in the primary source materials, and instead largely a creation of the secondary literature. The present article sets out to trace its development in the secondary literature from the nineteenth century onwards. Research materials: Briefly noting the portrayal of Nogai’s role in the relevant primary sources – the Rus’ chronicles, Mamluk historians, Rashīd al-Dīn and Marco Polo – then notes the contrast in the most prominent secondary literature on the Golden Horde of the last century, including d’Ohsson, Veselovskij, Vernadsky, Spuler through to Vásáry and Favereau. Research results and novelty: Much of the basis for the modern idea of Nogai the Khanmaker owes to Veselovskij’s 1922 biography of Nogai, built upon by the influential histories on the Golden Horde by Vernadsky and Spuler. Later scholars have combined these accounts, exaggerating claims of his prominence with each succeeding generation and accepting, unquestioned, Nogai’s modern status as the near-total master of the Jochid ulus.